2020
DOI: 10.1002/jper.20-0372
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic potential of peri‐implant crevicular fluid microRNA‐21‐3p and microRNA‐150‐5p and extracellular vesicles in peri‐implant diseases

Abstract: Background To explore the diagnostic usefulness of extracellular vesicles (EVs), and their subpopulations (micro‐vesicles and exosomes), and microRNAs (miRNA‐21‐3p, miRNA‐150‐5p, and miRNA‐26a‐5p) in peri‐implant crevicular fluid (PICF) of subjects with healthy, peri‐implant mucositis and peri‐implantitis implants. Methods A total of 54 patients were enrolled into healthy, peri‐implant mucositis, and peri‐implantitis groups. PICF samples were collected, EVs subpopulations (MVs and Exo) were isolated and charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…RANKL is one of the most extensively studied biomarkers in relation to bone metabolism and has been shown to be a valuable biomarker for determination of bone destruction in periodontal and peri-implant disease [ 10 , 21 ]. The results of the current study regarding RANKL level in PICF is in line with available evidence which showed increased expression of RANKL in sites with peri-implant mucositis and peri-implantitis compared to healthy sites [ 22 , 23 ]. These results indicate that RANKL could be one of the biomarkers which can be used to monitor potential progression of peri-implant diseases.…”
Section: Discussionsupporting
confidence: 89%
“…RANKL is one of the most extensively studied biomarkers in relation to bone metabolism and has been shown to be a valuable biomarker for determination of bone destruction in periodontal and peri-implant disease [ 10 , 21 ]. The results of the current study regarding RANKL level in PICF is in line with available evidence which showed increased expression of RANKL in sites with peri-implant mucositis and peri-implantitis compared to healthy sites [ 22 , 23 ]. These results indicate that RANKL could be one of the biomarkers which can be used to monitor potential progression of peri-implant diseases.…”
Section: Discussionsupporting
confidence: 89%
“…Extracellular vesicles (micro-vesicles and exosomes) are secreted vesicles with membrane structures, which protect the contents from degradation and enter the recipient cell. Extracellular vesicles have been reported as a novel strategy for the exogenous addition of miRNAs ( Song et al, 2019 ; Chaparro et al, 2021 ). It is necessary to explore the effects of miRNAs delivered by extracellular vesicle on diseases and promote the clinical application of miRNAs on tumors and other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs), for example, are small endogenous sequences of noncoding RNAs (ncRNAs) responsible for specific regulation of gene expression in a post-transcriptional manner [ 14 ]. They are involved in biological processes, such as immune-inflammatory response, bone metabolism, cell replication, and apoptosis [ 15 ]. They are already extensively employed for the early diagnosis, prognosis, and personalized therapies of oncologic and genetic diseases, but they have still been scarcely explored in dental implantology [ 16 ].…”
Section: Introductionmentioning
confidence: 99%